Fluorescence behaviour of 2-, 3- and 4-amino-1, 8-naphthalimides: effects of the substitution positions of the amino functionality on the photophysical properties. Issue 10 (15th August 2018) - Wang, Lei; Fujii, Mayu; Yamaji, Minoru; Okamoto, Hideki
Abstract : 2-Amino-1, 8-naphthalimide showed blue fluorescence independent of the microenvironment of the solvents whereas the corresponding 3- and 4-amino derivatives displayed marked positive solvatofluorochromism. Abstract : The absorption and fluorescence spectra of a series of 1, 8-naphthalimide derivatives incorporating the amino functionality at the 2-, 3- and 4-positions of the naphthalene ring (2APNI, 3APNI and4APNI, respectively) were systematically investigated in various solvents and in the solid state. The fluorescence spectra of2APNI were insensitive to solvent polarity and intermolecular hydrogen-bonding even in a protic medium such as methanol. Thus, 2APNI displayed blue fluorescence with a moderate fluorescence quantum yield ( λ Fmax = 420–445 nm, Φ F 0.2–0.3) in the solvents investigated. In contrast, the fluorescence spectra of3APNI and4APNI were strongly solvent dependent showing positive solvatofluorochromism with large Stokes shifts. Upon increasing the solvent polarity, the fluorescence colours changed from blue in hexane ( λ Fmax = 429 nm) to orange-yellow in methanol ( λ Fmax = 564 nm) for3APNI, and from blue in hexane ( λ Fmax = 460 nm) to yellow in methanol ( λ Fmax = 538 nm) for4APNI . The fluorescence quantum yields of3APNI and4APNI decreased with increasing solvent polarity. In the solid state, APNI s displayed red-shifted fluorescence emission compared to that in solution ( λ Fmax = 541 nm for2APNI, 575 nm for3APNI, and 561 nm for4APNI ) and the fluorescence quantum yields in the solid state were lower than those in solution.